An FMRI-Compatible Symbol Search Task. (20th March 2015) - Liebel, Spencer W.; Clark, Uraina S.; Xu, Xiaomeng; Riskin-Jones, Hannah H.; Hawkshead, Brittany E.; Schwarz, Nicolette F.; Labbe, Donald; Jerskey, Beth A.; Sweet, Lawrence H.
Abstract: Our objective was to determine whether a Symbol Search paradigm developed for functional magnetic resonance imaging (FMRI) is a reliable and valid measure of cognitive processing speed (CPS) in healthy older adults. As all older adults are expected to experience cognitive declines due to aging, and CPS is one of the domains most affected by age, establishing a reliable and valid measure of CPS that can be administered inside an MR scanner may prove invaluable in future clinical and research settings. We evaluated the reliability and construct validity of a newly developed FMRI Symbol Search task by comparing participants' performance in and outside of the scanner and to the widely used and standardized Symbol Search subtest of the Wechsler Adult Intelligence Scale (WAIS). A brief battery of neuropsychological measures was also administered to assess the convergent and discriminant validity of the FMRI Symbol Search task. The FMRI Symbol Search task demonstrated high test–retest reliability when compared to performance on the same task administered out of the scanner ( r =.791; p <.001). The criterion validity of the new task was supported, as it exhibited a strong positive correlation with the WAIS Symbol Search ( r =.717; p <.001). Predicted convergent and discriminant validity patterns of the FMRI Symbol Search task were also observed. The FMRI Symbol Search task is a reliable and valid measure of CPS in healthy older adults and exhibits expected sensitivity to the effects of age on CPS performance. ( JINS, 2015, 22, 1–8)